2011
DOI: 10.5038/2375-0901.14.3.7
|View full text |Cite
|
Sign up to set email alerts
|

What Do Passengers Do During Travel Time? Structured Observations on Buses and Trains

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…van de Waerden et al, 2009;Russell et al, 2011;Ettema et al, 2012;Gripsrud and Hjortol, 2012;Frie et al, 2015).…”
Section: 1unclassified
“…van de Waerden et al, 2009;Russell et al, 2011;Ettema et al, 2012;Gripsrud and Hjortol, 2012;Frie et al, 2015).…”
Section: 1unclassified
“…Nevertheless, their research also shows that the importance passengers place on using mobile devices is small when compared to other factors, such as schedule convenience. Russell et al (2011) observed bus and train riders in New Zealand, concluding that bus travelers are less apt to use mobile devices than train riders.…”
Section: Relevant Literaturementioning
confidence: 99%
“…[14,19,37,43,44,49,53,60]. Travel time can be seen as time that has been saved, or a pleasant time where the vehicle becomes a living space in its own right [49,51] and during which a variety of activities can be done, thus making it worthwhile -even productive [16,38,51,59].…”
Section: Introductionmentioning
confidence: 99%